Polyurethane diaphragm as well as preparation method and application thereof

By mixing and curing the polyurethane prepolymer, solvent, lithium salt and curing agent, and soaking it with crown ether solution and lithium salt solution, the obtained polyurethane separator prepared has high ionic conductivity, solving the problem of low electrical transmission efficiency of existing lithium-ion battery separators and reducing the battery weight and electrolyte usage.

CN119674440AActive Publication Date: 2025-03-21GUANGZHOU HAOYI NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510192326.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-21
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have low electrical transmission efficiency, large amount of electrolyte used and heavy weight, and poor affinity and wettability of electrolytes, which affects the performance of lithium-ion batteries.

Method used

Polyurethane prepolymer, solvent, lithium salt and curing agent are mixed and cured to make a polyurethane film, and is soaked by crown ether solution and lithium salt solution to form a polyurethane separator with high ionic conductivity.

Benefits of technology

It improves the transmission efficiency of lithium ions, reduces the battery weight, reduces the use of electrolyte, and improves the overall performance of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674440A_ABST
    Figure CN119674440A_ABST
Patent Text Reader

Abstract

The invention provides a polyurethane diaphragm as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) reacting isocyanate with polyol to obtain a polyurethane prepolymer; (2) mixing the polyurethane prepolymer prepared in the step (1), a solvent, a lithium salt and a curing agent to obtain slurry; (3) curing the slurry prepared in the step (2) to obtain a polyurethane film; and (4) treating the polyurethane film prepared in the step (3) by adopting a crown ether solution, and soaking by adopting a lithium salt solution to obtain the polyurethane diaphragm. The polyurethane film provided by the invention has the characteristics of promotion of lithium ion transmission, high electric transmission efficiency and good ionic conductivity, can reduce the usage amount of electrolyte in battery preparation, and greatly reduces the weight of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a polyurethane diaphragm and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are the most widely used and most mature secondary battery system, mainly composed of positive electrode materials, negative electrode materials, separators, current collectors, and electrolytes. Among them, the separator is the medium that separates the positive and negative electrodes inside the battery. It can prevent short circuits inside the battery and facilitate the passage of lithium ions, playing an irreplaceable role.

[0003] The existing lithium-ion battery separators are mainly polyolefin separators, made of polyethylene and / or polypropylene. Although polyolefin separators are porous and can achieve ion conductivity, polyethylene and / or polypropylene themselves are not conductive, which restricts the electrical transmission efficiency of polyolefin separators. By soaking the polyolefin separators with a large amount of electrolyte in the preparation of lithium-ion batteries, the lack of electrical transmission efficiency can be compensated, but it will cause a large amount of electrolyte to be used and the battery weight to be large. In addition, polyolefin separators also have problems such as poor electrolyte affinity and wettability, insufficient ion conductivity in liquid electrolytes, and low lithium ion migration numbers, which seriously affect the performance of lithium-ion batteries.

[0004] Therefore, it is necessary to develop a membrane with high ionic conductivity. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a polyurethane membrane and a preparation method and application thereof. The polyurethane membrane has the characteristics of high ion conductivity.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a polyurethane diaphragm, the preparation method comprising the following steps:

[0008] (1) reacting isocyanate and polyol to obtain a polyurethane prepolymer;

[0009] (2) mixing the polyurethane prepolymer prepared in step (1), a solvent, a lithium salt and a curing agent to obtain a slurry;

[0010] (3) curing the slurry obtained in step (2) to obtain a polyurethane film;

[0011] (4) The polyurethane film obtained in step (3) is treated with a crown ether solution and then immersed in a lithium salt solution to obtain the polyurethane diaphragm.

[0012] In the present invention, a polyurethane prepolymer, a solvent, a lithium salt and a curing agent are mixed and cured to form a polyurethane film. Crown ether and lithium ions have a complexation reaction. After being treated with a crown ether solution and soaked in a lithium salt solution, the prepared polyurethane diaphragm has the characteristics of promoting lithium ion transmission, high electrical transmission efficiency and good ion conductivity. At the same time, the amount of electrolyte used in battery preparation can be reduced, and the weight of the battery can be greatly reduced.

[0013] In the present invention, in step (4), the polyurethane film obtained in step (3) is treated with a crown ether solution, which can remove lithium ions in the polyurethane film and form ion channels of lithium ions on the polyurethane film. On this basis, the polyurethane film is further soaked in a lithium salt solution to fully wet the ion channels, which is beneficial to improving the ionic conductivity of lithium ions.

[0014] Preferably, the isocyanate in step (1) includes any one of dicyclohexylmethane-4,4'-diisocyanate (HMDI), xylylene diisocyanate (XDI), tetramethyl metaxylylene diisocyanate (TMXDI), hexamethylene diisocyanate (HDI) or pentamethylene diisocyanate (PDI), or a combination of at least two thereof.

[0015] Preferably, the polyol in step (1) comprises any one of polypropylene glycol, polyethylene glycol or polyethylene oxide propylene oxide glycol, or a combination of at least two thereof.

[0016] Preferably, the number average molecular weight of the polyol in step (1) is 1000-2000, for example, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800 or 1900.

[0017] Preferably, the solvent in step (2) comprises any one of acetone, butanone, isopropanol or propylene glycol monomethyl ether, or a combination of at least two thereof.

[0018] Preferably, the lithium salt in step (2) comprises lithium bis(trifluoromethanesulfonyl imide) (LiN(CF 3 SO 2 ) 2 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ) or lithium bis(sulfonyl)imide (LiN(SO 2 F) 2 ) or a combination of at least two of them.

[0019] Preferably, the curing agent in step (2) includes an alcohol curing agent and / or an amine curing agent.

[0020] Preferably, the alcohol curing agent includes 1,4-butanediol (BDO) and / or 1,4-cyclohexanedimethanol (CHDM).

[0021] Preferably, the amine curing agent includes any one of 4,4'-methylenebis(2-chloroaniline), diethyltoluenediamine or dimethylthiotoluenediamine, or a combination of at least two thereof.

[0022] Preferably, the mass percentage concentration of the crown ether in the crown ether solution in step (4) is 8% to 13%, for example, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% or 12.5%.

[0023] Preferably, the crown ether in the crown ether solution in step (4) includes 12-crown-4 and / or benzo-12-crown-4-ether.

[0024] In the present invention, the crown ether and the lithium ion in the crown ether solution are complexed. Since the more negative the electrostatic potential of the molecular surface site is, the more likely it is that an electrophilic reaction will occur, the electrostatic potential of the crown ether "crown center" site is the most negative. After the lithium ion is complexed with the crown ether, it is located at the "crown center" of the crown ether. Taking benzo-12-crown-4-ether as an example, the structural schematic diagram of benzo-12-crown-4-ether complexing lithium ions is as follows: Figure 1 shown.

[0025] Preferably, the solvent in the crown ether solution in step (4) comprises acetonitrile.

[0026] Preferably, the concentration of the lithium salt in the lithium salt solution in step (4) is 0.5-1.5 mol / L, for example, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L or 1.4 mol / L.

[0027] Preferably, the lithium salt in the lithium salt solution in step (4) comprises any one of lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate or lithium bis(fluorosulfonyl)imide, or a combination of at least two thereof.

[0028] Preferably, the solvent in the lithium salt solution in step (4) includes acetonitrile.

[0029] Preferably, the molar ratio of isocyanate to polyol in step (1) is (1.5-2.5):1, for example, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1 or 2.4:1.

[0030] Preferably, the reaction temperature in step (1) is 80-90°C (e.g., 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C or 89°C, etc.), and the reaction time is 8-10 h (e.g., 8.2 h, 8.4 h, 8.6 h, 8.8 h, 9.0 h, 9.2 h, 9.4 h, 9.6 h or 9.8 h, etc.).

[0031] Preferably, the mass content of -NCO groups in the polyurethane prepolymer in step (1) is 4.5wt% to 6.5wt%, for example, 4.7wt%, 4.9wt%, 5.1wt%, 5.3wt%, 5.5wt%, 5.7wt%, 5.9wt%, 6.1wt% or 6.3wt%.

[0032] Preferably, the mixing in step (2) is carried out in an environment with a dew point of less than -40°C (eg, -45°C, -50°C, -55°C, -60°C, -65°C or -70°C, etc.).

[0033] Preferably, in step (2), taking the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent as 100%, the mass of the polyurethane prepolymer is 30% to 40%, for example, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38% or 39%.

[0034] Preferably, in step (2), the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent is 100%, and the mass of the solvent is 30% to 45%, for example, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43% or 44%.

[0035] Preferably, in step (2), the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent is 100%, and the mass of the lithium salt is 10% to 20%, for example, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18% or 19%.

[0036] In the present invention, the total mass of the polyurethane prepolymer, solvent, lithium salt and curing agent is 100%, and the mass of the lithium salt is preferably 10% to 20%. If the mass proportion of the lithium salt is too high, the pore size of the ion channel will be too large, causing damage to the ion channel and even causing the circulation of the electrolyte to cause internal failure of the battery; if the mass proportion of the lithium salt is too low, the ion channel is too small and the ionic conductivity is not high.

[0037] Preferably, in step (2), the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent is 100%, and the mass of the curing agent is 4% to 10% (for example, 5%, 6%, 7%, 8% or 9%), and more preferably 6% to 8%.

[0038] Preferably, the mixing in step (2) specifically comprises stirring and mixing the polyurethane prepolymer, solvent and lithium salt obtained in step (1) evenly, and then adding the curing agent and stirring and mixing evenly.

[0039] Preferably, the curing in step (3) includes a first curing and a second curing.

[0040] Preferably, the first curing temperature is 80-100°C, for example, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C or 98°C.

[0041] Preferably, the first curing time is 0.5 to 1 h, for example, 0.55 h, 0.6 h, 0.65 h, 0.7 h, 0.75 h, 0.8 h, 0.85 h, 0.9 h or 0.95 h, etc.

[0042] Preferably, the second curing temperature is 100-130°C, such as 105°C, 110°C, 115°C, 120°C, 125°C, etc.

[0043] Preferably, the second curing time is 10 to 16 h, for example, 11 h, 12 h, 13 h, 14 h or 15 h.

[0044] Preferably, the polyurethane film has a thickness of 17-23 μm, for example, 18 μm, 19 μm, 20 μm, 21 μm or 22 μm.

[0045] Preferably, the treatment with the crown ether solution in step (4) specifically comprises immersing the polyurethane film in the crown ether solution and performing ultrasonic cleaning.

[0046] Preferably, the temperature of the ultrasonic cleaning is 20-30°C, for example, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C or 29°C.

[0047] Preferably, the ultrasonic cleaning time is 4 to 10 h, for example, 5 h, 6 h, 7 h, 8 h or 9 h.

[0048] Preferably, the immersion temperature of the lithium salt solution in step (4) is 20-30°C (for example, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C or 29°C), and the immersion time is 12-20 h (for example, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h or 19 h).

[0049] In the present invention, the reaction schematic diagram of the reaction in step (1) is shown in Formula I, and the reaction schematic diagram of the reaction in step (3) is shown in Formula II or Formula III.

[0050] Formula Ⅰ.

[0051] In Formula I, “ "Isocyanate" " is a polyol," " is a polyurethane prepolymer.

[0052] Formula II.

[0053] In Formula II, “ " is an alcohol curing agent.

[0054] Formula III.

[0055] In Formula III, “ " is an amine curing agent.

[0056] In the present invention, in step (1), isocyanate and polyol react, wherein isocyanate groups and hydroxyl groups react, and the molar amount of isocyanate groups in the isocyanate is greater than the molar amount of hydroxyl groups in the polyol, so that the obtained polyurethane prepolymer contains isocyanate groups to facilitate the subsequent curing reaction. The product in formula I is only an example of a polyurethane prepolymer containing isocyanate groups.

[0057] In the present invention, in step (2), the polyurethane prepolymer, solvent, lithium salt and curing agent are physically mixed to form a slurry, and the polyurethane prepolymer, lithium salt and curing agent are uniformly mixed so that the lithium salt is uniformly distributed in the polyurethane film prepared later. Taking the total mass of the polyurethane prepolymer, solvent, lithium salt and curing agent as 100%, the mass of the polyurethane prepolymer is 30%-40%, and the mass of the solvent is 30%-45%, which helps to make the slurry have a relatively low viscosity and achieve uniform mixing, while avoiding excessive solvent content leading to a long subsequent curing time; the mass of the lithium salt is 10%-20%, the filling amount is appropriate, and an appropriate amount of pore structure can be formed to avoid a high lithium salt filling amount, the ion channel aperture will be too large, causing ion channel damage, and even causing the circulation of electrolyte to cause internal battery failure, or the lithium salt filling amount is low, the ion channel aperture will be too small, the number of ion channels is small, which is not conducive to the circulation of lithium ions; the mass of the curing agent is 4%-10%, which can make the polyurethane prepolymer fully react and achieve curing.

[0058] In the present invention, step (3) solidifies the slurry obtained in step (2) to form a polyurethane film. During the curing process, the isocyanate group in the polyurethane prepolymer reacts with the hydroxyl group in the alcohol curing agent or the amino group in the amine curing agent to form a polymer that becomes the structural skeleton of the polyurethane diaphragm, and the lithium salt is filled between the structural skeletons. At a relatively high curing temperature, the solvent in the slurry evaporates to form a polyurethane film.

[0059] In the present invention, in step (4), the polyurethane film obtained in step (3) is treated with a crown ether solution. The crown ether has a complexation with lithium ions and can remove lithium ions in the polyurethane film. The lithium ions removed from the polyurethane film form ion channels of lithium ions on the polyurethane film. Then, the polyurethane film is immersed in a lithium salt solution to fully wet the ion channels and introduce freely movable lithium ions, which is beneficial to improving the ion conductivity.

[0060] In a second aspect, the present invention provides a polyurethane diaphragm, which is prepared by the preparation method described in the first aspect.

[0061] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the polyurethane separator as described in the second aspect.

[0062] Preferably, the lithium ion battery is a liquid battery.

[0063] Compared with the prior art, the present invention has the following beneficial effects:

[0064] In the present invention, a polyurethane film prepared by mixing and curing a polyurethane prepolymer, a solvent, a lithium salt and a curing agent is treated with a crown ether solution and soaked in a lithium salt solution. The polyurethane diaphragm prepared has the characteristics of promoting lithium ion transmission, high electrical transmission efficiency and good ion conductivity. At the same time, it can reduce the amount of electrolyte used in battery preparation and significantly reduce the weight of the battery. The ion conductivity of the polyurethane diaphragm is ≥3×10 -4 S / cm, preferably, the ionic conductivity is ≥5×10 -4 S / cm. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 It is a schematic diagram of the structure of benzo-12-crown-4-ether complexed lithium ion;

[0066] Figure 2 This is the infrared spectrum of xylylene diisocyanate;

[0067] Figure 3 is the infrared spectrum of polypropylene glycol;

[0068] Figure 4 is the infrared spectrum of the polyurethane prepolymer prepared in step (1) of Example 2;

[0069] Figure 5 is the infrared spectrum of the polyurethane film obtained in step (3) of Example 2;

[0070] Figure 6 is the adsorption-desorption curve measured after the polyurethane diaphragm prepared in step (4) of Example 2 is dried;

[0071] Figure 7 This is a physical picture of the polyurethane diaphragm obtained in step (4) of Example 2. DETAILED DESCRIPTION

[0072] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0073] Example 1

[0074] This embodiment provides a polyurethane diaphragm and a preparation method thereof, the preparation method comprising the following steps:

[0075] (1) Mixing isocyanate (dicyclohexylmethane-4,4'-diisocyanate) and polyol (polyethylene glycol, number average molecular weight of 1500) and reacting them at 85°C for 12 h to obtain a polyurethane prepolymer, wherein the feed ratio of isocyanate to polyol is controlled so that the mass content of -NCO groups in the polyurethane prepolymer is 5.5wt%;

[0076] (2) In a dry environment with a dew point of 45° C., the polyurethane prepolymer prepared in step (1), the solvent (acetone) and the lithium salt (lithium bis(trifluoromethanesulfonylimide)) are stirred and mixed uniformly, and then a curing agent (1,4-butanediol) is added and stirred and mixed uniformly to obtain a slurry with the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent being 100%, the mass of the polyurethane prepolymer being 35%, the mass of the solvent being 40%, the mass of the lithium salt being 20%, and the mass of the curing agent being 5%;

[0077] (3) coating the slurry obtained in step (2) on a release film (PET release film), and transferring the slurry into a drying oven for first curing and second curing. The first curing temperature is 85°C for 1 h; the second curing temperature is 120°C for 13 h, to obtain a polyurethane film with a thickness of 20 μm;

[0078] (4) The polyurethane film obtained in step (3) is immersed in a crown ether solution for ultrasonic cleaning at a temperature of 25° C. for 8 h, and then immersed in a lithium salt solution at a temperature of 25° C. for 15 h to obtain the polyurethane membrane.

[0079] The crown ether solution is prepared by mixing benzo-12-crown-4-ether and acetonitrile, wherein the mass percentage concentration of benzo-12-crown-4-ether is 10%;

[0080] The lithium salt solution is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and acetonitrile, wherein the concentration of lithium bis(trifluoromethanesulfonyl)imide is 1 mol / L.

[0081] Example 2

[0082] This embodiment provides a polyurethane diaphragm and a preparation method thereof, the preparation method comprising the following steps:

[0083] (1) Mixing isocyanate (xylylene diisocyanate) and polyol (polypropylene glycol, number average molecular weight of 1000) and reacting them at 80°C for 14 h to obtain a polyurethane prepolymer, wherein the feed ratio of isocyanate to polyol is controlled so that the mass content of -NCO groups in the polyurethane prepolymer is 4.5wt%;

[0084] (2) In a dry environment with a dew point of 45° C., the polyurethane prepolymer prepared in step (1), the solvent (methyl ethyl ketone) and the lithium salt (lithium bis(trifluoromethanesulfonyl imide)) are stirred and mixed uniformly, and then a curing agent (1,4-butanediol) is added and stirred and mixed uniformly to obtain a slurry with the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent being 100%, the mass of the polyurethane prepolymer being 33%, the mass of the solvent being 43%, the mass of the lithium salt being 16%, and the mass of the curing agent being 8%;

[0085] (3) coating the slurry obtained in step (2) on a release film (PET release film), and transferring the slurry to a drying oven for first curing and second curing. The first curing temperature was 90° C. for 0.5 h; the second curing temperature was 110° C. for 13 h, and a polyurethane film was obtained with a thickness of 17 μm.

[0086] (4) The polyurethane film obtained in step (3) is immersed in a crown ether solution for ultrasonic cleaning at a temperature of 20° C. for 10 h, and then immersed in a lithium salt solution at a temperature of 20° C. for 20 h to obtain the polyurethane diaphragm.

[0087] The crown ether solution is prepared by mixing benzo-12-crown-4-ether and acetonitrile, wherein the mass percentage concentration of benzo-12-crown-4-ether is 8%;

[0088] The lithium salt solution is prepared by mixing lithium bis(trifluoromethanesulfonyl imide) and acetonitrile, wherein the concentration of lithium bis(trifluoromethanesulfonyl imide) is 0.8 mol / L.

[0089] Example 3

[0090] This embodiment provides a polyurethane diaphragm and a preparation method thereof, the preparation method comprising the following steps:

[0091] (1) mixing isocyanate (hexamethylene diisocyanate) and polyol (polyethylene oxide propylene oxide diol, wherein the molar ratio of ethylene oxide segment to propylene oxide segment is 2:3, and the number average molecular weight is 1000), and reacting at 90° C. for 11 h to obtain a polyurethane prepolymer, wherein the feed ratio of isocyanate to polyol is controlled, and the mass content of -NCO groups in the polyurethane prepolymer is 6.5wt%;

[0092] (2) In a dry environment with a dew point of 45° C., the polyurethane prepolymer prepared in step (1), the solvent (methyl ethyl ketone) and the lithium salt (lithium bis(trifluoromethanesulfonyl imide)) are stirred and mixed uniformly, and then a curing agent (1,4-butanediol) is added and stirred and mixed uniformly to obtain a slurry with the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent being 100%, the mass of the polyurethane prepolymer being 30%, the mass of the solvent being 40%, the mass of the lithium salt being 20%, and the mass of the curing agent being 10%;

[0093] (3) coating the slurry obtained in step (2) on a release film (PET release film), and transferring the slurry to a drying oven for first curing and second curing. The first curing temperature is 100° C. for 0.5 h; the second curing temperature is 120° C. for 13 h. A polyurethane film is obtained with a thickness of 23 μm.

[0094] (4) The polyurethane film obtained in step (3) is immersed in a crown ether solution for ultrasonic cleaning at a temperature of 30° C. for 6 h, and then immersed in a lithium salt solution at a temperature of 30° C. for 12 h to obtain the polyurethane diaphragm.

[0095] The crown ether solution is prepared by mixing benzo-12-crown-4-ether and acetonitrile, wherein the mass percentage concentration of benzo-12-crown-4-ether is 13%;

[0096] The lithium salt solution is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and acetonitrile, wherein the concentration of lithium bis(trifluoromethanesulfonyl)imide is 1.5 mol / L.

[0097] Example 4

[0098] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between the embodiment 1 and the embodiment 1 is that the lithium salt (lithium bistrifluoromethanesulfonyl imide) in step (2) is replaced by a lithium salt (lithium trifluoromethanesulfonate) of the same mass, and the lithium salt solution in step (4) is prepared by mixing lithium trifluoromethanesulfonate and acetonitrile, wherein the concentration of lithium trifluoromethanesulfonate is 1 mol / L, and the other conditions are the same as those in embodiment 1.

[0099] Example 5

[0100] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between the embodiment 1 and the embodiment 1 is that the lithium salt (lithium bistrifluoromethanesulfonyl imide) in step (2) is replaced by a lithium salt (lithium bisfluorosulfonyl imide) of the same mass, and the lithium salt solution in step (4) is prepared by mixing lithium bisfluorosulfonyl imide and acetonitrile, wherein the concentration of lithium bisfluorosulfonyl imide is 1 mol / L, and the other conditions are the same as those in embodiment 1.

[0101] Example 6

[0102] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the crown ether solution in step (4) is prepared by mixing 12-crown ether-4 and acetonitrile, wherein the mass percentage concentration of 12-crown ether-4 is 10%, and other conditions are the same as those in embodiment 1.

[0103] Example 7

[0104] This embodiment provides a polyurethane diaphragm and a preparation method thereof, which differs from Embodiment 1 in that the curing agent (1,4-butanediol) is replaced with a curing agent of the same mass (1,4-cyclohexanedimethanol), and other conditions are the same as those in Embodiment 1.

[0105] Example 8

[0106] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the curing agent (1,4-butanediol) is replaced with a curing agent of the same mass (4,4'-methylenebis(2-chloroaniline)), and other conditions are the same as those in embodiment 1.

[0107] Example 9

[0108] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the curing agent (1,4-butanediol) is replaced with a curing agent of the same mass (diethyltoluenediamine), and other conditions are the same as those in embodiment 1.

[0109] Example 10

[0110] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the curing agent (1,4-butanediol) is replaced with a curing agent of the same mass (dimethylthiotoluene diamine), and other conditions are the same as those in embodiment 1.

[0111] Embodiment 11

[0112] The present embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between the present embodiment and embodiment 1 is that in step (1), the polyol (polyethylene glycol, number average molecular weight is 1500) is replaced by polyol (polyethylene glycol, number average molecular weight is 800), and the feed ratio of isocyanate and polyol is controlled so that the mass content of -NCO groups in the polyurethane prepolymer is still 5.5wt%. Other conditions are the same as those in embodiment 1.

[0113] Example 12

[0114] The present embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between the present embodiment and embodiment 1 is that in step (1), the polyol (polyethylene glycol, number average molecular weight is 1500) is replaced by polyol (polyethylene glycol, number average molecular weight is 2400), and the feed ratio of isocyanate and polyol is controlled so that the mass content of -NCO groups in the polyurethane prepolymer is still 5.5wt%. Other conditions are the same as those in embodiment 1.

[0115] Embodiment 13

[0116] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that in step (2), the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent is 100%, the mass of the lithium salt is adjusted to 5%, and the mass of the solvent is adjusted to 55%. Other conditions are the same as those in embodiment 1.

[0117] Embodiment 14

[0118] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that in step (2), the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent is 100%, the mass of the lithium salt is adjusted to 25%, and the mass of the solvent is adjusted to 35%. Other conditions are the same as those in embodiment 1.

[0119] Embodiment 15

[0120] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the mass percentage concentration of benzo-12-crown-4-ether in the crown ether solution in step (4) is adjusted to 5%, and other conditions are the same as those in embodiment 1.

[0121] Example 16

[0122] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the mass percentage concentration of benzo-12-crown-4-ether in the crown ether solution in step (4) is adjusted to 15%, and other conditions are the same as those in embodiment 1.

[0123] Embodiment 17

[0124] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the concentration of lithium bis(trifluoromethanesulfonyl)imide in the lithium salt solution in step (4) is adjusted to 0.3 mol / L, and other conditions are the same as those in embodiment 1.

[0125] Embodiment 18

[0126] This embodiment provides a polyurethane diaphragm and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the concentration of lithium bis(trifluoromethanesulfonyl)imide in the lithium salt solution in step (4) is adjusted to 2 mol / L, and other conditions are the same as those in embodiment 1.

[0127] Comparative Example 1

[0128] This comparative example provides a polyurethane diaphragm and a preparation method thereof. The difference between the comparative example and Example 1 is that step (4) does not include the step of soaking in a lithium salt solution, and other conditions are the same as those in Example 1.

[0129] Comparative Example 2

[0130] This comparative example provides a polyurethane diaphragm and a preparation method thereof. The difference between the comparative example and Example 1 is that step (4) does not include the step of immersing in a crown ether solution for ultrasonic cleaning, and the other conditions are the same as those in Example 1.

[0131] Comparative Example 3

[0132] This comparative example provides a polyurethane diaphragm and a preparation method thereof, which differs from Example 1 in that step (4) is not included, and other conditions are the same as those of Example 1.

[0133] Comparative Example 4

[0134] This comparative example provides a polyurethane diaphragm and a preparation method thereof. The difference between the comparative example and Example 1 is that no lithium salt is added in step (2), the total mass of the polyurethane prepolymer, the solvent and the curing agent is 100%, the mass of the solvent is adjusted to 60%, and the other conditions are the same as those in Example 1.

[0135] The polyurethane membranes provided in the above Examples 1-18 and Comparative Examples 1-4 were tested for ion conductivity, and the test results are shown in Table 1 below:

[0136] Table 1

[0137]

[0138] From the content of Table 1, it can be seen that the ionic conductivity of the polyurethane membranes provided in Examples 1 to 18 is ≥3×10 -4 S / cm.

[0139] In Example 2, the infrared spectrum of xylene diisocyanate is as follows: Figure 2 As shown, the infrared spectrum of polypropylene glycol (number average molecular weight is 1000) is as follows Figure 3 As shown, the infrared spectrum of the polyurethane prepolymer prepared in step (1) is as follows Figure 4 As shown by Figure 2-4 contrast, Figure 4 Middle 3327cm -1 The peak generated at 1720 cm is the characteristic absorption peak of the NH bond in the carbamate group. -1 The peak at 2265cm is the characteristic absorption peak of the C=O bond in the urethane group, indicating that xylene diisocyanate and polypropylene glycol react to form a polyurethane prepolymer; -1 The peak generated at is the characteristic absorption peak of -NCO group, indicating that -NCO group still exists in the obtained polyurethane prepolymer. The infrared spectrum of the polyurethane film obtained in step (3) is as follows: Figure 5 As shown in the figure, the characteristic absorption peak of the -NCO group disappears, and the characteristic absorption peaks of the NH bond in the carbamate group and the C=O bond in the carbamate group exist, 3325cm -1 The peak produced at is the characteristic absorption peak of hydroxyl group, indicating the presence of carbamate group and hydroxyl group in the prepared polyurethane film.

[0140] The polyurethane membrane obtained in step (4) is dried and the adsorption-desorption curve measured by BET low-temperature nitrogen adsorption method is as follows: Figure 6As shown, the diameter of the mesopores in the polyurethane separator was measured to be 1.4 nm, indicating that there are ion channels for lithium ions in the polyurethane separator.

[0141] The actual picture of the polyurethane diaphragm obtained in Example 2 is as follows: Figure 7 shown.

[0142] Compared with Example 1, if the amount of lithium salt added in step (2) is too little (Example 13), the ion conductivity of the prepared polyurethane membrane will be reduced; if the amount of lithium salt added in step (2) is too much (Example 14), the ion channel in the prepared polyurethane membrane will be slightly damaged and the ion conductivity will also decrease. It can be seen that in the present invention, by controlling the amount of lithium salt added in step (2), the performance of the prepared polyurethane membrane is better.

[0143] Compared with Example 1, if the mass percentage concentration of the crown ether in the crown ether solution in step (4) is too low (Example 15), the lithium ion replacement is insufficient and the ionic conductivity of the prepared polyurethane membrane will be significantly reduced; if the mass percentage concentration of the crown ether in the crown ether solution in step (4) is too high (Example 16), the ionic conductivity of the prepared polyurethane membrane will not change significantly, but the preparation cost will be increased.

[0144] Compared with Example 1, if the concentration of lithium salt in the lithium salt solution in step (4) is too low (Example 17), the ion channel is not fully wetted, and the ionic conductivity of the prepared polyurethane membrane will be reduced; if the concentration of lithium salt in the lithium salt solution in step (4) is too high (Example 18), the ion channel is fully wetted, and the ionic conductivity of the prepared polyurethane membrane will not change much if the concentration of lithium salt in the lithium salt solution is further increased, but the preparation cost will be increased.

[0145] Compared with Example 1, if step (4) does not include the step of soaking in a lithium salt solution (Comparative Example 1), the ion conductivity of the prepared polyurethane membrane is low because the ion channels are not wetted; if step (4) does not include the step of soaking in a crown ether solution for ultrasonic cleaning (Comparative Example 2), the ion conductivity of the prepared polyurethane membrane is reduced; if step (4) is not included (Comparative Example 3), the conductivity of the prepared polyurethane membrane is greatly reduced because lithium ion exchange channels are not prepared. It can be seen that the polyurethane membrane prepared by the method of the present invention has better performance.

[0146] Compared with Example 1, no lithium salt is added in step (2) (Comparative Example 4), and the ionic conductivity of the prepared polyurethane membrane is very poor.

[0147] In summary, the polyurethane membrane prepared by mixing and curing a polyurethane film made of a polyurethane prepolymer, a solvent, a lithium salt and a curing agent, treating the polyurethane film with a crown ether solution and soaking the film with a lithium salt solution has the characteristics of promoting lithium ion transmission, high electrical transmission efficiency and good ion conductivity.

[0148] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a polyurethane diaphragm and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a polyurethane diaphragm, characterized in that: The preparation method comprises the following steps: (1) reacting isocyanate and polyol to obtain a polyurethane prepolymer; (2) mixing the polyurethane prepolymer prepared in step (1), a solvent, a lithium salt and a curing agent to obtain a slurry; (3) curing the slurry obtained in step (2) to obtain a polyurethane film; (4) The polyurethane film obtained in step (3) is treated with a crown ether solution and then immersed in a lithium salt solution to obtain the polyurethane diaphragm.

2. The preparation method according to claim 1, characterized in that: The isocyanate in step (1) includes any one of dicyclohexylmethane-4,4'-diisocyanate, xylylene diisocyanate, tetramethyl-m-xylylene diisocyanate, hexamethylene diisocyanate or pentamethylene diisocyanate, or a combination of at least two thereof; The polyol in step (1) comprises any one of polypropylene glycol, polyethylene glycol or polyethylene oxide propylene oxide glycol or a combination of at least two thereof; The number average molecular weight of the polyol in step (1) is 1000-2000.

3. The preparation method according to claim 1, characterized in that: The solvent in step (2) includes any one of acetone, butanone, isopropanol or propylene glycol monomethyl ether, or a combination of at least two thereof; The lithium salt in step (2) includes any one of lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate or lithium bis(fluorosulfonyl)imide, or a combination of at least two thereof; The curing agent in step (2) includes an alcohol curing agent and / or an amine curing agent; The alcohol curing agent includes 1,4-butanediol and / or 1,4-cyclohexanedimethanol; The amine curing agent includes any one of 4,4'-methylenebis(2-chloroaniline), diethyltoluenediamine or dimethylthiotoluenediamine, or a combination of at least two thereof.

4. The preparation method according to claim 1, characterized in that: The mass percentage concentration of the crown ether in the crown ether solution of step (4) is 8% to 13%; The crown ether in the crown ether solution of step (4) includes 12-crown-4 and / or benzo-12-crown-4-ether; The solvent in the crown ether solution in step (4) includes acetonitrile; The concentration of lithium salt in the lithium salt solution in step (4) is 0.5-1.5 mol / L; The lithium salt in the lithium salt solution of step (4) comprises any one of lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate or lithium bis(fluorosulfonyl)imide or a combination of at least two thereof; The solvent in the lithium salt solution in step (4) includes acetonitrile.

5. The preparation method according to claim 1, characterized in that: The reaction temperature in step (1) is 80-90°C and the reaction time is 10-16 h; The mass content of -NCO groups in the polyurethane prepolymer in step (1) is 4.5wt%~6.5wt%.

6. The preparation method according to claim 1, characterized in that: The mixing in step (2) is carried out in an environment with a dew point of less than -40°C; In step (2), the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent is 100%, and the mass of the polyurethane prepolymer is 30% to 40%; In step (2), the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent is 100%, and the mass of the solvent is 30% to 45%; In step (2), the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent is 100%, and the mass of the lithium salt is 10% to 20%; In step (2), the total mass of the polyurethane prepolymer, the solvent, the lithium salt and the curing agent is 100%, and the mass of the curing agent is 4% to 10%; The mixing in step (2) specifically comprises stirring and mixing the polyurethane prepolymer, solvent and lithium salt obtained in step (1) evenly, and then adding a curing agent and stirring and mixing evenly.

7. The preparation method according to claim 1, characterized in that: The curing in step (3) includes a first curing and a second curing; The temperature of the first curing is 80-100°C; The first curing time is 0.5 to 1 h; The temperature of the second curing is 100-130°C; The second curing time is 10 to 16 hours.

8. The preparation method according to claim 1, characterized in that: The step (4) of treating with a crown ether solution specifically includes immersing the polyurethane film in a crown ether solution and performing ultrasonic cleaning; The temperature of the ultrasonic cleaning is 20-30°C; The ultrasonic cleaning time is 4 to 10 hours; The temperature of the lithium salt solution used for immersion in step (4) is 20-30° C. and the time is 12-20 h.

9. A polyurethane diaphragm, characterized in that: The polyurethane diaphragm is prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The lithium ion battery comprises the polyurethane separator as claimed in claim 9.

Citation Information

Patent Citations

  • Manufacturing method of polyurethane separating film for lithium sulfur battery

    CN109962199A

  • Preparation method of high-selectivity lithium-magnesium separation membrane

    CN113893713A

  • Polyurea and / or polyurethane-based gel electrolyte as well as preparation method and application thereof

    CN116565307A

  • Nanofiltration membrane for extracting lithium from salt lake and preparation method of nanofiltration membrane

    CN117563440A

  • Lithium secondary battery

    KR1020010073589A